2022
DOI: 10.3389/fpsyg.2022.926539
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Should I Go? Risk Perception and Use of Local Public Transport During the COVID-19 Pandemic

Abstract: In light of the climate crisis, the transport sector needs to be urgently transformed and the number of users of local public transport needs to be increased. However, the first year of the COVID-19 pandemic severely affected public transport with passenger numbers declining up to 80% in Germany. In addition to a general decrease in mobility during lockdowns, we can observe a shift in decision-making in regards to modes of transportation, with public transport losing out. We argue that this change in behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The importance of rebuilding trust in public transportation was a recurrent theme in the literature [13,[23][24][25]54], and our study underscores this challenge. The observed mode shift has significant implications for urban planning and transportation policies.…”
Section: D46mentioning
confidence: 64%
See 1 more Smart Citation
“…The importance of rebuilding trust in public transportation was a recurrent theme in the literature [13,[23][24][25]54], and our study underscores this challenge. The observed mode shift has significant implications for urban planning and transportation policies.…”
Section: D46mentioning
confidence: 64%
“…The study [53] conducted in Gdansk, Poland revealed that the Covid-19 pandemic could lead to subjective safety concerns regarding public transport, resulting in a significant proportion (25 %) of participants losing confidence in its safety. The survey conducted in Germany with the participation of 918 individuals revealed that users are expected to experience lingering fear of infection related to public transport even after the pandemic [54].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a growing body of literature on medical travel that addresses various aspects of the phenomenon, including its economic and health resource implications, demand and supply, the role of the state, and the pros and cons of promoting it. 8 However, there is a gap in the literature regarding medical travel, specifically the lack of an integrated regulation 9 , 10 and its implementation, especially in the context of medical escort services in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Strong regulations positively impact public perception of the safety and quality of public transportation, including medical evacuation services. 10 Robust governing regulations are integral to well-organized business processes that deliver high-quality services to the public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation